Homogeneous environmental selection mainly determines the denitrifying bacterial community in intensive aquaculture water - Zheng, Xiafei; Yan, Zhongneng; Zhao, Chenxi; He, Lin; Lin, Zhihua; Liu, Minhai (Frontiers in Microbiology, 2023)
Nitrate reduction by napA (encodes periplasmic nitrate reductase) bacteria and nitrous oxide reduction by nosZ (encodes nitrous oxide reductase) bacteria play important roles in nitrogen cycling and removal in intensive aquaculture systems. This study investigated the diversity, dynamics, drivers, and assembly mechanisms of total bacteria as well as napA and nosZ denitrifiers in intensive shrimp aquaculture ponds over a 100day period. Alpha diversity of the total bacterial community increased significantly over time. In contrast, the alpha diversity of napA and nosZ bacteria remained relatively stable throughout the aquaculture process. The community structure changed markedly across all groups over the culture period. Total nitrogen, phosphate, total phosphorus, and silicate were identified as significant drivers of the denitrifying bacterial communities. Network analysis revealed complex co-occurrence patterns between total, napA, and nosZ bacteria which fluctuated over time. A null model approach showed that, unlike the total community dominated by stochastic factors, napA and nosZ bacteria were primarily governed by deterministic processes. The level of determinism increased with nutrient loading, suggesting the denitrifying community can be manipulated by bioaugmentation. The dominant genus Ruegeria may be a promising candidate for introducing targeted denitrifiers into aquaculture systems to improve nitrogen removal. Overall, this study provides important ecological insights into aerobic and nitrous oxide-reducing denitrifiers in intensive aquaculture, supporting strategies to optimize microbial community structure and function.